HARAPAN ORANG TUA MEMILIH PROGRAM KESETARAAN UNTUK BELAJAR ANAKNYA DI PKBM KAK SETO PEKANBARU - Aldawiah, Siti Mutiah; iIrja, Desti; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : This study is entitled Hope parents choose an equality program to study their children in PKBM Kak Seto Pekanbaru which shows the following phenomena, 1. There are still parents who do not understand the importance of learning for children, so that many children whose work is unclear and does not change family economy. 2. There are still parents who do not understand the importance of the value that will be obtained if the child learns, so that many children lack confidence when they want to do something, 3. There are still parents who do not understand the importance of trust, so many children are less open to people old age. From this phenomenon it can be concluded that there are still parents who do not understand the importance of choosing an equality program to study their children. This is estimated because of the varied levels of education, employment and economic status. So the formulation of the problem in this study is how high is the expectation that parents choose an equality program to study their children in PKBM Kak Seto? This type of research is descriptive research, this is in accordance with the opinion of Sugiyono (2012: 11) with a quantitative approach using simple random sampling technique (questionnaire random sampling) through questionnaires, which amounted to 50 items statement. Data obtained from respondents totaling 20 people for the trial sample and 38 people for the study sample. After the questionnaire is tested, there are 2 invalid items, and the researcher discards invalid statements, so that 48 valid statement items are used.ndonesia to.Keywords: Hope, parents.